If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 2) = 528 Reorder the terms: x(2 + x) = 528 (2 * x + x * x) = 528 (2x + x2) = 528 Solving 2x + x2 = 528 Solving for variable 'x'. Reorder the terms: -528 + 2x + x2 = 528 + -528 Combine like terms: 528 + -528 = 0 -528 + 2x + x2 = 0 Factor a trinomial. (-24 + -1x)(22 + -1x) = 0Subproblem 1
Set the factor '(-24 + -1x)' equal to zero and attempt to solve: Simplifying -24 + -1x = 0 Solving -24 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + -1x = 0 + 24 Combine like terms: -24 + 24 = 0 0 + -1x = 0 + 24 -1x = 0 + 24 Combine like terms: 0 + 24 = 24 -1x = 24 Divide each side by '-1'. x = -24 Simplifying x = -24Subproblem 2
Set the factor '(22 + -1x)' equal to zero and attempt to solve: Simplifying 22 + -1x = 0 Solving 22 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + -1x = 0 + -22 Combine like terms: 22 + -22 = 0 0 + -1x = 0 + -22 -1x = 0 + -22 Combine like terms: 0 + -22 = -22 -1x = -22 Divide each side by '-1'. x = 22 Simplifying x = 22Solution
x = {-24, 22}
| 13x-213=6x-10 | | 6x-7= | | 5x-4=13x-42 | | 3x+38=13x-42 | | x^2+x^5= | | 6n=10 | | 6x+27=13x-36 | | 226-5x=31x+22 | | 3+5x=-12 | | 4x+47=7x+11 | | -8+7=-1 | | 7+4(2c-1)= | | (2v^2)(7v)= | | 4(4c-1)-5=14c+7 | | 5x^2-3xy-8y^3=0 | | 12(x+4)=4(3x+5)+28 | | 5=r-4+5 | | 2v^2+7v= | | x^2+28=0 | | -11=-7+2y | | 1+x-2x=-5 | | 6(x-3)=-2x+30 | | 4t-11=2t-5 | | 2(y+3)=-2y+22 | | 4t-2=5(t+5) | | 2(x-1)=14x+16 | | (-25)-4x^2= | | 2(x+3)=-2y+22 | | 2(x-1)=-4x+28 | | 2(x-1)=-4x+16 | | 2x^2=56 | | 3(x-1)+28=-2x |